Pemasaran Produk UMKM Misscrip Melalui Penerapan Digital Marketing Oleh Damartrends - Mutiara Kalyaveda; Heidy Arviani (FKIP, Universitas Palangka Raya, 2023)
The digital market has become an important platform for Micro, Small and Medium Enterprises (MSMEs) to promote and market their products. This study aims to explore the application of digital marketing strategies to Misscrip SMEs by Damartrends in expanding market reach and increasing sales of their products. The results of the study show that Damartrends has successfully implemented a digital marketing strategy effectively to market MSME Misscrip products. The implementation of digital marketing involves using social media and websites to expand their reach and increase their brand visibility. In addition, Damartrends also utilizes paid advertising to increase their online visibility.